Philippine Academy of Medical Specialists Hospital, Binangonan - Ibanez, Robin Royce Y.
The Philippine Academy of Medical Specialists, a non-stock, non-profit medical organization, is composed of 43 chapters nationwide, 28 disciplines, 5 affiliate medical specialty organization and 2 affiliated basic science organizations. With goals of unifying, developing and assigning Medical Specialists throughout the Philippines, as well as maintaining the highest possible level of medical and scientific skills to better serve the people, the organization has taken it upon themselves to provide a venue that will cater to these objectives. Initially, the project was stated to be included in the urban planning development of the Laguna Lake, linking the surrounding cities and provinces with each other through easy to access tram ways and bridges. In a bid to hasten the completion of said goals, the organization has procured a site in the first class urban municipality of Binangonan Rizal, wherein they intend to design and build a well-equipped specialties hospital inclusive of a state of the art medical arts building, and medical landscaping. While adhering to the given assumptions and limitations, a thorough feasibility study was conducted to design the most applicable layout for the Main Hospital Building, Medical Arts Building, Parking Building, and Civic Spaces. All of which were designed to functionally integrate each component to provide a top-tier healthcare facility in Binangonan.